Mending the heart and mind during times of loss: a review of interventions to improve emotional well-being during spousal bereavement. Issue 2 (4th May 2018) - Shahane, Anoushka D.; Fagundes, Christopher P.; Denny, Bryan T.
Abstract: Spousal loss is one of life's greatest stressors. Bereaved spouses are at risk for aberrant cognitive and affective processing. Recent work in psychoneuroimmunology and cognitive neuroscience reveals physiological biomarkers and neural mechanisms underlying acute distress and grief during bereavement that may represent targets for future interventions. We review evidence from existing pharmacological and psychotherapeutic treatment approaches for normal bereavement, complicated grief, and bereavement-related depression. We propose promising future directions, namely the development and empirical validation of novel, personalised cognitive and neurostimulatory interventions to promote adaptive emotion regulation and reduce depressive symptoms following spousal loss. Future work may substantiate which interventions to improve emotional and physical health will be best matched to the needs of a particular surviving spouse.